Achieving Research-Informed Practice Amongst Teachers in Madrid and Catalonia: Findings From a Quantitative Analysis - Ion, Georgeta; Brown, Chris; López-Sirvent, Ernest (International Journal of Education Policy and Leadership, 2022)
Background: In Spain, as in many other countries, educational administrators are calling for schools and teachers to engage with research-informed teaching (RIT) to improve the quality of teaching and student outcomes. Despite this interest, schools’ and teachers’ engagement with research evidence is inconsistent, and studies exploring the factors affecting teachers’ and schools’ commitment to RIT, in the Spanish context, are undeveloped.Analysis: The authors analyzed a survey sample of 462 teachers in 204 Spanish schools to identify teacher and school characteristics that determine teachers’ likelihood of engaging in evidence-informed educational practice (EIP). This analysis explores variables such as teachers’ concepts of research, their self-efficacy to understand and conduct educational research, and the influence of school organizational variables.Findings: Teachers seem reluctant to use research in class practice. Whether research is seen as relevant to their immediate or short-term needs, combined with the capacity to use data research evidence, appears to be a decisive factor for those engagedwith research.